P. Knox, Aids, ancestors and salvation: local beliefs in Christian ministry to the sick - Pieter Verster (Acta Theologica)
From text: Taking his cue from the Kairos document, Knox engages Aids in the Southern African context, especially the context of Lesotho. The role of the veneration of the ancestors in seeking a possible solution to the challenges posed by dealing with the illness forms a substantial part of his discussion. A prophetic theology in line with the Kairos document’s suggestions is then proposed.